Sabiston textbook of surgery : the biological basis of modern surgical practice - Sabiston, David C.; Townsend, Courtney M.; Perioperative Care. (Philadelphia : Saunders, 2004)
Electronic image collection to accompany Sabiston Textbook of Surgery--Accompanying CD-ROM
Includes bibliographical references and index
Keywords: Electronic image collection to accompany Sabiston Textbook of Surgery--Accompanying CD-ROM; Surgical Procedures, Operative; Surgery